Role and impotrance of Camargue cattle and horse breeds in France - Abayné Hamar, Enikő; Tóthné Maros, Katalin; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
In France, the Camargue region is a special area for the preservation of cultural and animal husbandry traditions, partly, because the Camargue cattle and horses are kept here. The Camargue is located in the delta of the two branches of the Rhône River, which flows into the Mediterranean Sea, in the south of France. Its climate is Mediterranean, with cool, rainy winters and hot, dry summers. The image of the Camargue landscape is basically determined by the water. We presented the place of origin and breeding area of the two species, their utilization and their role in our society. The research results were also introduced briefly. The professional, cultural and social work that takes place here can be an example of the preservation and utilization of the values that exist in a given area.